2022
DOI: 10.3389/fped.2022.822108
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Screen Time and Body Mass Index Among Children and Adolescents: A Systematic Review and Meta-Analysis

Abstract: BackgroundThere is no summative quantitative study that report the difference in BMI in high screen user children and adolescents or give a difference in screen time in children and adolescents with obesity vs. children and adolescents without obesity. In the current meta-analysis we systematically summarized the association between obesity and screen time and meta-analyzed the results.MethodsA systematic search from Scopus, PubMed and Embase electronic databases. Studies that evaluated the association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
(89 reference statements)
1
7
0
Order By: Relevance
“…In recent years, there has been a significant increase in screen time among adolescents, which may have adverse effects on their health. Research has found a significant correlation between screen time and obesity among children [ 40 , 41 ]. Khan et al [ 42 ] found that excessive screen time of any type was associated with sleep difficulties among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a significant increase in screen time among adolescents, which may have adverse effects on their health. Research has found a significant correlation between screen time and obesity among children [ 40 , 41 ]. Khan et al [ 42 ] found that excessive screen time of any type was associated with sleep difficulties among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis of Fang et al [36] showed that children and adolescents with an ST greater than 2 h/d had a 1.67 times higher risk of overweight and obesity than those with an ST of less than 2 h/d. Wu et al [37] further conducted a quantitative study. The results showed that the BMI of children and adolescents with an ST greater than 2 h/d was 0.7 kg/m 2 higher than that of children and adolescents with an ST of less than 2 h/d, and the ST of obese children and adolescents was 0.3 h/d higher than that of normal children.…”
Section: Discussionmentioning
confidence: 99%
“…Increased screen time (characterized as the use of mobile phones, tablets, video games, and television [1]) is associated with an increased risk for the development of overweight and obesity in children and adolescents [2]. This association can be explained by replacing activities with higher energy expenditure by sedentary behavior [3] and by the greater consumption of high-calorie density foods such as ultra-processed foods [3,4].…”
Section: Introductionmentioning
confidence: 99%